Functions of emergency response team in emergency preparedness and response plan for improving campus environment resilience - Sabri, Syikh Sazlin Shah; Mohd. Hussain, Mohd. Ramzi; Abdul Hamed, Sapiah; Rusli, Nazrul (Otago Polytechnic, 2025)
Emergency Response Teams (ERT) play a pivotal role in safeguarding campus communities during emergency crises as an emergency management system support. This study employs analytical review articles to examine the roles and functions of ERTs within the Emergency Preparedness and Response Plan (EPRP) framework in higher education institutions. Through a comprehensive review of thirty scholarly articles, guidelines, and institutional protocols, the research synthesizes key insights into the strategic integration of ERTs in campus emergency management. The findings highlight the importance of proactive planning, legal compliance, and coordinated response mechanisms in enhancing institutional resilience. By mapping ERT roles against national safety standards and university-level implementation practices, the study underscores the necessity of structured training, documentation, and stakeholder engagement. Ultimately, this paper advocates for a culturally contextualized and legally grounded approach to emergency preparedness, positioning ERTs as central agents in mitigating risks and promoting sustainable campus safety.